The Process of Activating Public Space through Grey Space and Lingering Space in the Old Town Area of Semarang - Maria Damiana Nestri Kiswari; Tri Hesti Mulyani (Jurnal Lingkungan Binaan Indonesia, 2026)
Heritage revitalization commonly emphasizes physical improvements, while the socio-spatial processes shaping the vitality of public spaces remain insufficiently explained in relational terms. This study examines how the configuration of grey space generates lingering conditions during the public space activation process in Semarang’s Old City. An exploratory case-study approach was employed, using structured spatial observation and behavioural mapping, to identify morphological typologies and patterns of temporary-staying activities. The findings indicate that edge quality, spatial subdivision, scale proportion, shading, and connectivity with active functions contribute to longer-duration lingering. However, this relationship is not deterministic; the interplay between spatial configuration and temporal dynamics shapes lingering intensity. Lingering functions as a transitional phase that links morphological structure and social interaction, thereby supporting the vitality of public space in a gradual, contextual manner. This study positions grey space as an analytical framework for understanding the relational process of public space activation within heritage contexts, extending the discourse beyond purely physical and descriptive approaches toward a more process-oriented perspective.